A preliminary study of cushion properties of a 3D printed thermoplastic polyurethane Kelvin foam. Issue 5 (21st June 2017) - Ge, Changfeng; Priyadarshini, Lakshmi; Cormier, Denis; Pan, Liao; Tuber, Jonathan
Abstract : The cells in conventional packaging foams have random size and orientation, and the energy‐absorbing behaviour of these foams is determined by the collective contribution of different sizes of cells. In contrast to the random nature of stochastic foams, 3D printing technologies allow engineers to design and produce foams having engineered cellular structures. In this study, engineered cellular structures based on the classic Kelvin 1887 model were 3D printed in 30 × 30 × 30 mm thermoplastic polyurethane cubes with a repeating size of 216 unit cells. One hundred consecutive cyclic compression tests were performed to assess the 3D printed foam's resilience and energy absorption characteristics. The stress‐strain curve of the 3D printed thermoplastic polyurethane foam indicated viscoelastic behaviour and a Mullins effect indicative of resilient rubber. A long wave buckling mode was observed during cyclic compression cycles due to the Kelvin structure. The cushion factor computed from the stress‐strain curve was close to that of a metal spring with linear elasticity. The combination of the 3D printed foam's resilience, its much lower density than rubber, and the complete geometric freedom of the engineered cellular structures offer designers the potential to create high‐performance cushion materials tailored for packaging applications. Abstract : In this study, engineered cellular structures based on the classic Kelvin 1887 model were 3D printed thermoplastic polyurethane cubes. The cushion factor computed from the stress‐strain curve was close to that of a metal spring with linear elasticity. The combination of the 3D printed foam's resilience and the complete geometric freedom of the engineered cellular structures offer designers the potential to create high‐performance cushion materials tailored for packaging applications.